Pengaruh Kualitas Informasi Akuntansi, Akuntabilitas dan Transparansi Pelaporan Keuangan Terhadap Tingkat Penerimaan Dana Zakat - Agihidayantari, Efri; Kurniawan, Putu Sukma (Vokasi : Jurnal Riset Akuntansi, 2020)
The purpose of this study is to determine the efect quality of accounting information, accountabillity and transparency in financial report on the level of recipt of zakat funds at the BAZNAS of Buleleng Regency. This research is a quantitative studying in which the source of the data comes from primarry data in the form of distributing questionnaires directly and via google form to respondents. The population in this study is  muzakki who pay their zakat through the BAZNAS of Buleleng Regency. The sample selected by purposive technique and obtained a total sample is 182 people. Analysis of the data used consists of: data quality test, descriptive analysis, classic assumption test, and hypothesis testing. Where the hypothesis test includes multiple linear regression test, t test and test the coeficient of determination with the help of SPSS version 24 for windows. The results of this study indicate that 1. Quality of Accounting Information has a positive efect on the level of receipt of zakat funds 2. Accountability has a positive efect on the level of receipt of zakat funds and 3. Transparency of financial reporting has a positive efect on the level of receipt of zakat funds.